Work-Life Balance dan Kepuasan Kerja: Mediasi oleh Stres Kerja - Sekar Dwi Ningrum; Friska Utami Saraswati Sembiring; Holisane Angela br. Keliat; Delyani Fatmawina Pulungan (Universitas Kristen Maranatha, 2026)
High job demands often hinder the balance between work and personal life, potentially triggering stress and reducing job satisfaction. This quantitative study aims to examine the effect of work-life balance (WLB) on job satisfaction, with job stress as a mediating variable. The research subjects consisted of 263 employees (55.89% male, (n=147); 44.11% female, n=116) at a beverage distribution company, with an average age of 31.59 years (range 20–50 years), selected via random sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS. The instruments used included the Indonesian adaptations of the work-life balance scale by Maimunah et al. (2024) (α=0.864), the job stress scale by Vandiya & Etikariena (2018) (α=0.830), and the job satisfaction scale by Nolandari et al. (2016) (α=0.70). Results indicated that all items maintained good quality with outer loading values > 0.70. The findings show that work-life balance has a significant negative effect on job satisfaction (β = -0.438; p < 0.001) and a positive relationship with job stress (β= 0.675; p< 0.001). Job stress also significantly affects job satisfaction (β= -0.298; p < 0.001). Furthermore, job stress was proven to significantly mediate the relationship between work-life balance and job satisfaction (β= -0.201; p=0.001).